Perancangan Sistem Informasi Perpustakaan Sekolah Berbasis Web SD Swata Islam Terpadu Daar Al Ulum Kab. Asahan - Eliza Sutanti (Repeater : Publikasi Teknik Informatika dan Jaringan, 2025)
School libraries have a strategic role in supporting the teaching and learning process, but the manual management system is a major obstacle in service. This research aims to design a web-based library information system to improve the efficiency and quality of services at SD Darul Ulum, Kisaran District. The research method used is a qualitative method with observation and survey techniques to collect data. The results showed that the web-based information system developed was able to transform the manual process into a more effective digital system, with the main features including membership management, digital book catalog, loan and return system, and report management. The system provides easy access to information, improves data accuracy, speeds up the administration process, and reduces the risk of losing documents. The implementation of a web-based library information system is proven to significantly improve the quality of school library services.